Pencarian Informasi Mahasiswa Teknologi Pangan Unpad: Sebuah Kajian Teori Anomalous State of Knowledge (ASK) - Metya Kusumadiyanty; Aunilla Nailalmarom; Prijana Prijana; Evi Nursanti Rukmana (Universitas Sebelas Maret Library, 2025)
This study aimed to identify factors that influence information searches by students of Food Technology, Padjadjaran University, related to knowledge and skills in accessing information with the Anomalous State of Knowledge (ASK) theory. The study was conducted using a quantitative method, with research data collected through questionnaires consisting of closed questions (matrix questions) and open questions (contingency questions) as research instruments. The results of this study stated that (1) there is a significant relationship between the breadth of knowledge factor and information search actions. (2) there is a significant relationship between the information search skill factor and information access. This significant relationship is proven by the significance value of t <0.05 (result t <0.001). (3) The factor of students' ability to connect new information with information searches does not have a significant relationship, with a significance value of t > 0.05 (result t = 0.44), in the sense that students tend to experience knowledge anomalies, by the ASK Theory (Anomalous State of Knowledge). Then, the researcher suggests that students can always search for information to improve their knowledge and skills by utilizing technological developments (access to digital library services and other learning aids) and involving librarians in helping to improve knowledge and skills to find information to help in the learning process. This is because searching for information is not only limited to one source but can also be from comparing or adding other sources of information.